REPRESENTATION OF FEMALE MASCULINITY IN NETFLIX SERIES’ SWEET HOME - Lisa Oktiviani Tanaga; Eni Maryani; Evi Rosfiantika (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Sweet Home is a South Korean Netflix film series featuring predominantly masculine female characters. In South Korea, films or series with openly feminist issues receive backlash from parties who strongly oppose feminism. However, this film series gained success, and its masculine female characters received various praises. This study aims to identify the representation of female masculinity in the film. This study applied qualitative research using John Fiske’s semiotic analysis. It found that there are codes of masculinity in the female characters at the level of reality. The female characters are strong, athletic, active individuals, leaders, technicians, and adventurers. At the level of representation, the female characters are identified as masculinity as they are subjects who can determine attitudes and make decisions. Then, if the women in the film are allowed to speak, act, and behave like men, the women are superior to men. The female characters represent a belief that men are the opposite of women. The women need to appear to defeat or to be more significant, which can be categorized as radical feminism at the ideological level.